2022
DOI: 10.1021/acs.molpharmaceut.1c00944
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of 1α,25-Dihydroxyvitamin D3 and CYP24A1 Inhibitor VID400 by Nanofiber Dressings Promotes Endogenous Antimicrobial Peptide LL-37 Induction

Abstract: Surgical site infections represent a significant clinical problem. Herein, we report a nanofiber dressing for topical codelivery of immunomodulating compounds including 1α,25dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) and VID400, a CYP24A1 inhibitor in a sustained manner, for inducing the expression of the endogenous cathelicidin antimicrobial peptide (CAMP) gene encoding the hCAP18 protein, which is processed into the LL-37 peptide. Nanofiber wound dressings with coencapsulation of 1,25(OH) 2 D 3 and VID400 were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…[ 32,33 ] In our previous studies, we demonstrated the sustained delivery of immunomodulating compounds (1,25(OH) 2 D 3 and/or VID400) promotes the expression of LL‐37 in monocytic cells suggesting potential for preventing surgical site infection. [ 20 ] In this study, we demonstrated exosomes secreted by monocytic cells after treatment with VD 3 and VD 3 /VID400‐loaded PCL NF contained significantly elevated levels of hCAP18/LL‐37 which enhances their biological activities when compared to untreated cell exosomes. The main advantage of the present method of increasing hCAP18/LL‐37 in natural exosomes using immunomodulatory compounds is that one avoids direct encapsulation of LL‐37 peptide into exosomes using physical or chemical approaches as these processes may destabilize the peptide and compromise its biological activities.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…[ 32,33 ] In our previous studies, we demonstrated the sustained delivery of immunomodulating compounds (1,25(OH) 2 D 3 and/or VID400) promotes the expression of LL‐37 in monocytic cells suggesting potential for preventing surgical site infection. [ 20 ] In this study, we demonstrated exosomes secreted by monocytic cells after treatment with VD 3 and VD 3 /VID400‐loaded PCL NF contained significantly elevated levels of hCAP18/LL‐37 which enhances their biological activities when compared to untreated cell exosomes. The main advantage of the present method of increasing hCAP18/LL‐37 in natural exosomes using immunomodulatory compounds is that one avoids direct encapsulation of LL‐37 peptide into exosomes using physical or chemical approaches as these processes may destabilize the peptide and compromise its biological activities.…”
Section: Resultsmentioning
confidence: 79%
“…This result was consistent with the trend we found for cellular mRNA from treated U937 cells. [20] To determine whether the induced cathelicidin mRNA levels correlated with an increase in protein expression, we quantified cathelicidin protein levels in total exosome lysates using an ELISA. Figure 2B shows increased levels of hCAP18/LL-37 in exosomes derived from U937 cells after treatment with VD 3 and VD 3 /VID400 free drugs and their nanofiber formulations on days 3 and 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations